Conception, design, and fabrication of novel cost-effective partial-hand prosthetic devices for a quadrilateral individual with limb loss. (August 2019) - Ng, Yu Xuan Vanessa
Background and Aim: The author designed customized upper-limb prosthetic devices for a 22-year-old man with quadrilateral limb loss. The devices were created to meet his functional requirements, while remaining cost-effective. What made this solution unique was that it utilized low-cost items that were easily sourced and maintained. Technique: Devices with polypropylene sockets, wooden positional fingers from an artist's wooden hand and a metal extension plate were conceptualized and manufactured. The patient gave written consent to the publication of information and photographs in this report. Discussion: The devices allowed the individual to complete tasks he desired to be able to perform independently, which included using a computer mouse, aided by the devices. The devices utilized were low-cost and easily accessible materials, such as polypropylene and wood, to cater to financial constraints. The final design had positional fingers and an extension plate to restore surface area for grip, support, and opposition to enable the execution of daily tasks of living. Clinical relevance: A cost-effective method of fabricating partial-hand devices with easily accessible materials is described. The resulting devices were successful at restoring the upper-limb surface area for improved grip, support, and opposition for performance of daily tasks.